Pest control using virus as control agent: A mathematical model - Pathak, Sweta; Maiti, Alakes (Nonlinear Analysis: Modelling and Control, 2012)
It is now well recognised that biocontrol of pests is one of the best ecofriendly alternative for pest control. In this paper we have studied dynamical behaviours of a model for biocontrol of pests, where it is assumed that the pest is affected by a virus. Boundedness and stability of the model are studied. The effect of time-delay is investigated. Numerical simulations are carried out to illustrate our analytical findings. It is observed that the time-delay has a regulatory impact on the system. Biological implications of our results are discussed.